PENDEKATAN ARSITEKTUR PERILAKU PADA PERANCANGAN MADU PLAYHOUSE UBUD BALI - Teresia Hanna Sanjaya (LPPM Institut Desain dan Bisnis Bali, 2023)
Children's learning ability, driven by the child's willingness to learn. This willingness is supported by a safe and comfortable space to explore, such as a Child Friendly City. In realizing a Child Friendly City, it is necessary to have Child Friendly Schools. Behavioral architecture approach will help assess a child's growth-learning space that is comfortable and safe. The purpose of this study was to examine the Design of Honey Playhouse, a Waldorf School in Ubud Bali, as well as the benefits of social or practical values, namely child-friendly design and learning methods. The theory used is Behavioral Architecture, and the Waldorf Learning Method. This study uses a qualitative approach. The collection technique was carried out by interviews, field observations, and online and offline documentation. The results showed that the behavioral architectural approach was carried out from the design concept to the finalization of the design, which in the end the school design grew together with school students.